Jackknife : New and Selected Poems - Beatty, Jan, 1952- (Book collections on Project MUSE., 2017)
In Jackknife: New and Selected Poems, Beatty travels the turns and collisions of over twenty years of work. She moves from first-person narratives to poems that straddle the page in fragments, to lines that sprawl with long lines of train tracks. Always landing in meaning, we are inside the body--not in a confessional voice, not autobiography--but arriving through the expanded, exploded image of many stories and genders. The new poems leap imagistically from the known world to the purely imagined, as in the voice in "Abortion with Gun Barrel": "I am the counselor, /there are cracks in the barrel of the gun/there is aiming/shots of sorrow--/ shots of light." Commitment to a rabid feminist voice continues, but arrival has a new ring to it, with beginnings rescripted: "I am a bastard./I walk around in this body of mine." Beatty's fascination with the highway and the breakout West jackknifes at the crossroads of the brutal and the white plains of loss--the body torn down and resurrected in the twenty first century.